2012
DOI: 10.1103/physrevb.85.024201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of spontaneous hole formation in thin polymeric films

Abstract: We show computationally that (molten) thin polymeric film containing nonequilibrium configurations originating from a solvent evaporation may develop holes spontaneously in the molten state, and that they appear delayed. Polymers above the glass transition temperature are liquids where the flow depends solely on the nonequilibrium configurations of the molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In addition to these factors, one can consider that a film has increased surface area, increased permeability to admitting and releasing of gas species, and increased thermal confinement over bulk samples. Finally, while it was noted that spontaneous hole formation of a melted thin film is of the order of 1 min, the formation time is dramatically reduced with lower molecular weight . Given that photolithographic patterning is based on breaking down the molecular weight of the polymeric resist, together with partial etching and thinning of the film, suggests that hole nucleation could also occur at a lower single pulse threshold, especially when there are multiple pulses that exceed the photolithographic exposure dose (e.g., those typical numbers of 20–30 mJ/cm 2 that are used in developing the stepper specifications in Table notes f, g.)…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to these factors, one can consider that a film has increased surface area, increased permeability to admitting and releasing of gas species, and increased thermal confinement over bulk samples. Finally, while it was noted that spontaneous hole formation of a melted thin film is of the order of 1 min, the formation time is dramatically reduced with lower molecular weight . Given that photolithographic patterning is based on breaking down the molecular weight of the polymeric resist, together with partial etching and thinning of the film, suggests that hole nucleation could also occur at a lower single pulse threshold, especially when there are multiple pulses that exceed the photolithographic exposure dose (e.g., those typical numbers of 20–30 mJ/cm 2 that are used in developing the stepper specifications in Table notes f, g.)…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Reiter et al found that the spontaneous hole nucleation rates at temperatures close to T g decreased with increased aging times at 50 °C for 40 nm thick 4.8 MDa PS films . Aging above T g also releases residual stress of spun on films from solvated polymers, which results in thickening of the films and spontaneous formation of holes. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stable polymer thin film is destabilized by the introduction of polar interactions. More informations on the surface topology observed with spontaneous hole development in thin polymeric films can be found elsewhere [22]. A 3 l droplet of THF (Tetrahydrofuran) is dropped off on the thin film surface.…”
mentioning
confidence: 99%